Análisis de mercado de leña y carbón de uso industrial y doméstico En Iquitos – Maynas Loreto, 2010 - Pezo Piña, Ingrid Anjhela (2011)
This market analysis aims to know the supply and demand of forest products, such as charcoal and firewood in the districts of Iquitos, San Juan, Belén and Punchana, this being the objective that the author has considered, having developed the market research based on basic primary and secondary information considering the establishments, consumers, volumes, purchase and sale centers, historical information of marketing and consumption. The results obtained show that there are 150 establishments that consume firewood and charcoal, of which 75% are active and are located in the ports of Moronacocha, Belén, Pampachica and Santa Clara de Nanay the demand for these products is based on 20 species for the firewood product and 27 species for charcoal. products extracted without the respective extraction permit granted by the Ministry of Agriculture by the populations settled in the different basins of the Amazon basin, the projected potential demand for firewood in 12 months, considers 3,315 M3, in the case of charcoal the projected annual demand reaches a total of 573, 739 Kg. It is concluded that the average production of firewood in the last 9 years (1996 - 2004) of the department of Loreto was 147,137 m3 which corresponds to the use of various species, the highest price is S/. 15.00 /bag and the lowest is S/. 5.00 /bag, 59% of coal consumers are supplied by a person who sells the product under the delivery modality, adding S/.1.00 per transport. 41% go to marketing centers. The most consumed species are Caimitillo, Humarí, Quinilla and Huacapurana, there are 66 establishments that consume firewood dedicated to the baking industry.